Caracterização mecânica de misturas asfálticas recicladas a quente - Lima, André Theophilo (2003)
Asphaltic pavement recycling is an effective and innovative technique that has been used for pavement restoration. The present work investigates the mechanical behavior of recycled hot asphaltic mixtures. The mixture design procedure used was the one adopted by the Asphalt Institute. The new binder was produced by PETROBRAS from the Venezuelan crude Bachaquero. For the characterization of both the new binder and the binder extracted and recovered from the recycled mixture, conventional tests such as penetration and viscosity were performed. These tests were performed along with the tests associated with the SUPERPAVE (Superior Performance Asphalt Pavements) specifications developed by the SHRP (Strategic Highway Research Program), an enhanced specification system for binders, aggregates, and mixture design based on pavement performance. Four different asphalt mixtures were analyzed in the study: without recycled material, with 10, 30 and 50% of recycled material from Washington Soares Avenue in Fortaleza. It was utilized a recycling agent (AR-75), produced by LUBNOR from a petroleum crude. The mixture mechanical properties determined in the laboratory were tensile strength, resilient modulus and fatigue life.